Analisa Maraknya Pemanfaatan Platform dalam Pengumpulan Zakat Melalui Prespektif Strukturasi Ala Giddens - Dwiki Faiz (LPPM STAI Diniyah Pekanbaru, 2021)
The potential and realization of zakat reported by BAZNAS as a government agency are still far from expectations. One indication that appears significantly as a cause of digital sociology is the increasing number of actors using platforms to collect zakat. This then needs to be explored further about its attention, considering the digitization will not be stopped as well. This review is analyzed using a qualitative approach with descriptive analysis through relevant literature study techniques in order to form conceptual/ new findings. The results of the review suggest that it’s easy to find support in the digital age for activism through the use of digital tools. Thus, it’s able to encourage other actors to be involved in seeking and collecting zakat. Like the two sides of the coin, the ease for muzaki in distributing zakat certainly occurs thanks to digitization. On the other hand, the supervision of related stakeholders down to the individual level as zakat/ alms collectors must be considered, especially from BAZNAS. If this is not the case, the distribution of zakat can be misused due to its own interests. In the future, because they can’t cut off the development of digital devices and actors, juggernaut symptoms will occur.